Biodiesel production from Jatropha curcas: Integrated process optimization - Huerga, Ignacio Roberto; Zanuttini, María Soledad; Gross, Martin Sebastian; Querini, Carlos Alberto (Elsevier, 2018)
Energy obtained from renewable sources has increased its participation in the energy matrix worldwide, and it is expected to maintain this tendency. Both in large and small scales, there have been numerous developments and research with the aim of generating fuels and energy using different raw materials such as alternative crops, algae and lignocellulosic residues. In this work, Jatropha curcas plantation from the North West of Argentina was studied, with the objective of developing integrated processes for low and medium sizes farms. In these cases, glycerine purification and meal detoxification processes represent a very high cost, and usually are not included in the project. Consequently, alternative uses for these products are proposed. This study includes the evaluation of the Jatropha curcas crop during two years, evaluating the yields and oil properties. The solids left after the oil extraction were evaluated as solid fuels, the glycerine and the meal were used to generate biogas, and the oil was used to produce biodiesel. The oil pretreatment was carried out with the glycerine obtained in the biodiesel production process, thus neutralizing the free fatty acid, and decreasing the phosphorous and water content